The effect of clonidine with bupivacaine on perioperative hemodynamics and post-operative analgesia in cesarean section cases - Kumar, Priti; Arya, Sangeeta; Singh, Sushil Kr.; Kumar, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cesarean section is the commonest procedure in Obstetric practice and postoperative pain can be a major factor for wound healing as well as mother and baby bonding. Spinal anesthesia is considered to be safest and easiest modality for cesarean section cases. Bupivacaine is the commonest drug given in spinal anesthesia, but many additive drugs have been introduced to cover post-operative analgesia. Clonidine is an alpha 2 agonist which can be used as an adjunct to heavy bupivacaine to extend analgesic effects. Methods: A randomized double-blind study was performed in 100 women undergoing elective cesarean section under spinal anaesthesia. After proper informed written consent patient undergoing cesarean section were divided by computerized method into group A (Given 10.0 mg 0.5% hyperbaric Bupivacaine) and Group B (Given 9.0 mg 0.5% hyperbaric bupivacaine and 30 μg clonidine). Results: Intraoperative hypotension is the most worrisome factor but it is transient and can be managed by ephedrine effectively. Intraoperative nausea and vomiting are slightly higher with clonidine as occurrence of hypotension is more. VAS scoring in post-operative period was better and need of first analgesic dose was much delayed in women been given clonidine with bupivacaine. Conclusions: Clonidine can be considered as adjunct in spinal anesthesia to extend post-op analgesic cover.